Intrusion Detection System Design Using Webcam And Artificial Intelligence In Aviation Polytechnic Medan - Permata, Dinda Suci Aliya; Hutabarat, Liber Tommy; Nasution, Darmeli (Peneliti.net, 2024)
Security systems are needed to maintain the safety and comfort of an area as well as on the Medan Aviation Polytechnic campus which requires a security system to protect the campus area. In an effort to maintain security and assist surveillance in the Medan Aviation Polytechnic campus area, an intrusion detection system is designed to monitor areas that are rarely reached by security officers to monitor any suspicious activity. The purpose of this design is to detect unauthorized activities so that it can assist security officers in maintaining security in the Medan Aviation Polytechnic campus environment. Artificial intelligence in this system helps to determine the target detected by the webcam, so that the buzzer will sound if the target detected is human. The results of this study show that this system is able to detect humans and Artificial Intelligence can detect humans so that the buzzer sounds when a human is detected.